Itch. (Eindhoven : Het Vagevuur, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks ?Redactie : Hemelrijken 18, 5612 LD Eindhoven ; vanaf (1997) 11 : Kanaaldijk Noord 11, 5613 DH Eindhoven
Nederlands
Periodiek